An alternative deal for potato growers in a contract farming system - A. Wiboonpongse (2018)
At the present time there is much controversy with regard to the equity of small-scale producers in the supply chain. It is widely believed that farmers in the transitional economies have difficulty in gaining market access. While contract farming is a direct mechanism for integrating small growers into the supply chain, the system is said to provide few advantages for growers. In particular, growers have expressed concerns regarding the equity of the contracts they sign with food processors and their economic security after the termination of the contract. This paper illustrates the significant change in farmers' practice from being contracted to non-contracted. This encouraged potato growers to negotiate a better deal and to access public sector support.